The Impact of Big Math for Little Kids on Children’s Number Skills - (:unkn) unknown (My University, 2021)
It is acknowledged that, of the math skills, the number skills are the most significant factor which affects math achievement in the forthcoming grades. Thus, it is critical to support the development of number skills early in life. The present study examines whether supplementing a global curriculum with the Big Math for Little Kids (BMLK) affects the growth of children’s number skills. Pretest-posttest experimental design was used. Seventy-seven kindergarten children (38 experimental; 39 comparison) participated in the study. For six weeks, children in the experimental group were exposed to the Ministry of National Education (MoNE) program plus the BMLK while those in the comparison group only experienced the MoNE program. Children’s number skills were measured by the Anatolian Early Childhood Mathematics Skills Scale (ANOMAT). Findings indicated that children who were exposed to the global MoNE curriculum supplemented with the BMLK had greater gains than did those who experienced only the MoNE curriculum. The results indicate that a global curriculum supplemented with a skill-based curriculum has a positive impact on children’s number skills.

Matematik becerilerinden sayı becerisinin ilerleyen yıllardaki matematik edinimini sağlayan en önemli etken olduğu bilinmektedir. Bu nedenle erken dönemde sayı becerilerinin gelişiminin desteklenmesi önemlidir. Bu çalışma, küresel bir öğretim programını, “Küçük Çocuklar İçin Büyük Matematik” programı ile desteklemenin çocukların sayı becerisi gelişimini etkileyip etkilemediğini incelemektedir. Çalışmada, öntest-sontest deneysel desen kullanılmıştır. Yetmiş yedi anasınıfı çocuğu (38 deney; 39 karşılaştırma) çalışmaya katılmıştır. Altı hafta boyunca deney grubunda yer alan çocuklar, Milli Eğitim Bakanlığı’nın (MEB) programı ve “Küçük Çocuklar İçin Büyük Matematik” programına katılırken karşılaştırma grubundakiler sadece MEB programını deneyimlemiştir. Çocukların sayı becerisi, Anadolu Okulöncesi Matematik Beceri Ölçeği (ANOMAT) ile ölçülmüştür. Bulgular, “Küçük Çocuklar İçin Büyük Matematik” programı ile desteklenen küresel MEB programına maruz kalan çocukların, sadece MEB programını deneyimleyenlere göre daha fazla gelişim gösterdiklerini ortaya koymuştur. Sonuçlar, beceriye dayalı bir öğretim programıyla desteklenen küresel bir öğretim programının çocukların sayı becerisi üzerinde olumlu bir etkisi olduğunu göstermektedir.
Küçük Çocuklar İçin Büyük Matematik” Programının Çocukların Sayı Becerisine Etkisi